2008
DOI: 10.2514/1.34205
|View full text |Cite
|
Sign up to set email alerts
|

Grid-Free Simulation of the Spatially Growing Turbulent Mixing Layer

Abstract: The spatially developing, unforced, turbulent mixing layer is simulated via a grid-free vortex method. Vortex filaments composed of straight tubes are used as the computational element with new vortex tubes produced as the filaments stretch. A loop removal algorithm serves as a de facto subgrid model limiting growth in the number of elements to practical levels. The computations are high resolution and well resolve the mixing layer from its unforced inception as a laminar flow through transition to a self-simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
(83 reference statements)
3
20
0
Order By: Relevance
“…All simulations show that the pre-transition primary vortices undergo localised interactions, which are particularly evident in Case D1 (Figure 7a) at x/θ i ≈ 220 and in Case D3 at x/θ i ≈ 180. The vortex structure visualised in these images is remarkably similar to that observed in other simulations of the pre-transition region of the mixing layer (Bernard 2008;Lesieur et al 1997), where the pre-transition structure takes a 'chain-link fence' appearance. There is no particular evidence for a 'streaky' streamwise structure which has been observed in experimental studies (Bernal and Roshko 1986;Bell and Mehta 1992), and has also been observed to co-exist with the chain-link fence structure in numerical simulations (Bernard 2008).…”
Section: Flow Visualisationsupporting
confidence: 85%
See 2 more Smart Citations
“…All simulations show that the pre-transition primary vortices undergo localised interactions, which are particularly evident in Case D1 (Figure 7a) at x/θ i ≈ 220 and in Case D3 at x/θ i ≈ 180. The vortex structure visualised in these images is remarkably similar to that observed in other simulations of the pre-transition region of the mixing layer (Bernard 2008;Lesieur et al 1997), where the pre-transition structure takes a 'chain-link fence' appearance. There is no particular evidence for a 'streaky' streamwise structure which has been observed in experimental studies (Bernal and Roshko 1986;Bell and Mehta 1992), and has also been observed to co-exist with the chain-link fence structure in numerical simulations (Bernard 2008).…”
Section: Flow Visualisationsupporting
confidence: 85%
“…The value of k 1 for Case D3 falls within the range of mixing layer thickness growth rate constants reported in the literature (Brown and Roshko 1974;Bernard 2008). When the flow development becomes inhibited by the spanwise domain extent in both cases D1 and D2, the momentum thickness growth rate decreases.…”
Section: Mean Flow Statisticssupporting
confidence: 81%
See 1 more Smart Citation
“…This localised pairing can be seen in the light colours in the plan view taking a corrugated appearance in this region of the flow. This type of localised pairing has been observed in many other simulations of the plane mixing later with a pseudo-random white noise fluctuation environment, 22,24,26 and is sometimes referred to as giving the vortex structure a chain-link fence appearance. Once the streamwise structure has formed, a further interaction between the primary vortices precipitates the transition to turbulence in the mixing layer.…”
Section: Large Scale Spanwise Structure a Flow Visualisationmentioning
confidence: 59%
“…23 Flow visualisation of the high Reynolds number simulated flow shows that streamwise vorticity develops in the mixing layer, and that the streamwise vorticity persists far into the turbulent region. 22,23,26,27 Evidence for the presence of statistically stationary streamwise vorticity, however, appears to be lacking in all of these spatially-developing mixing layer computations.…”
Section: Introductionmentioning
confidence: 99%